Apoptosis and in vivo models to study the molecules related to this phenomenon - Luchs,Adriana (2010)
ABSTRACT Apoptosis or programmed cell death is a physiological process, essential for eliminating cells in excess or that are no longer necessary to the organism, acting on tissue homeostasis, although the phenomenon is also involved in pathological conditions. Apoptosis promotes activation of biochemical pathways inside cells called caspase pathway, of the proteins responsible for the cleavage of several cell substrates, leading to cell death. Antiapoptotic members of the Bcl-2 family (B cell CLL/lymphoma 2), that belong to the intrinsic route of the activation of caspases, such as Bcl-xL (extra-large B-cell lymphoma) and Bcl-w (Bcl-2-like 2), act predominantly to prevent that pro-apoptotic members, such as Bax (Bcl-2-associated X protein) and Bak (Bcl-2 relative bak) lead to cell death. Antiapoptotic molecules are considered potentially oncogenic. Murine models are known to be valuable systems for the experimental analysis of oncogenes in vivo, and for the identification of pharmacological targets for cancer and to assess antitumor therapies. Given the importance of tumorigenesis studies on the immune responses to cancer and the possibility of investigating the participation of antiapoptotic molecules in tumor progression in vivo, the development of new models may be platforms for studies on tumorigenesis, immune antitumor responses, investigation of the ectopic expression of antiapoptotic molecules and immunotherapies for tumors.